Alpha-amylase, antioxidant, and anti-inflammatory activities of Eucheuma denticulatum (N.L. Burman) F.S. Collins and Hervey - Balasubramaniam, Vimala (Springer, 2016)
Eucheuma denticulatum is a red edible seaweed that grows in the East Malaysia coastal region. The objective of this study was to investigate the α-amylase, antioxidant and anti-inflammatory activities of E. denticulatum ethanol extract and its three fractions (n-hexane, ethyl acetate and acetone). α-Amylase activity was assessed by dinitrosalicylic acid (DNS) assay, while the antioxidant property was determined by oxygen radical absorbance capacity (ORAC) analysis. The anti-inflammatory effects of the seaweed samples were evaluated by nitric oxide (NO), interleukin-6 (IL-6), interleukin-1 (IL-1), tumor necrosis factor-alpha (TNF-α), and monocyte chemoattractant protein-1 (MCP-1) activities on the interferon-gamma/lipopolysaccharide (IFN-γ/LPS)-stimulated murine macrophage cell line (RAW 264.7) using Griess reaction and immunoassays, respectively. At 10 mg mL−1, E. denticulatum ethanol extract and three fractions inhibited α-amylase activities at variable levels. The highest (67 %) inhibition of α-amylase enzyme was by the ethanol crude extract. The three fractions showed inhibition with a mean of 42 %. Crude ethanol extracts also exhibited higher antioxidant capacity (36,400 ± 23.5 mol Trolox equivalent (TE) (100 g)−1) when compared to the fractions. Crude extract and fractions (1–100 μg mL−1), also exhibited anti-inflammatory activity without showing any cytotoxic effect to RAW 264.7 cells. The present study suggests that E. denticulatum has the potential to be a promising source of effective functional metabolite. An extensive research on the edible varieties would contribute to a better understanding of their importance as functional food.